Sexual function and predictors of sexual dysfunction among pregnant women receiving Primary Health Care - Aline Lara Cavalcante Oliva; Hanna Beatriz Bacelar Tibães; Giovana Gabriela Alves Taffarel; José Walter Fagundes de Souza Filho; Bruna Rayane Gomes Silva; Carolina Amaral Oliveira Rodrigues; Maria Fernanda Santos Figueiredo Brito (Revista Brasileira de Saúde Materno Infantil)
Abstract Objectives: to analyze sexual function and predictors of sexual dysfunction among pregnant women followed up in Primary Health Care in a city in the north of Minas Gerais. Methods: a cross-sectional, analytical study carried out with 1,279 pregnant women in Montes Claros/MG, between 2018 and 2019. Variable: dependent sexual satisfaction; independent variables: sociodemographic and obstetric characteristics, physical and mental health conditions and complaints during pregnancy. Results: the prevalence of sexual dysfunction was 27.4%. There was an association: between nine and 11 years of schooling (PR=1.08; 95%CI=1.03-1.14; p=0.002); or more than 11 years of schooling (PR=1.14; 95%CI=1.08-1.20; p<0.001); family income ≤ 1 minimum wage (PR=1.06; 95%CI=1.02-1.09;p<0.001); gestational complaint of dizziness (PR=1.54; 95%CI=1.23-1.92;p<0.001); low social support (PR=1.53; 95%CI=1.24-1.89;p<0.001); negative body image (PR=1.26; 95%CI=1.03-1.54; p=0.020); and presence of stress symptoms (PR=1.27; 95%CI=1.00-1.60; p<0.001). Conclusion: predictors of sexual dysfunction were identified in a significant proportion in pregnant women and were associated with sociodemographic factors (years of schooling); family income; obstetric factors (gestational complaints such as dizziness); social aspects such as low support; emotional aspects (negative body image) and the presence of stress symptoms. The results indicate the need for more studies on pregnant women in order to understand the causes of sexual dysfunction and provide guidance on interprofessional actions that promote sexual and reproductive health.